2000
DOI: 10.1002/jor.1100180314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze‐drying and gamma irradiation on the mechanical properties of human cancellous bone

Abstract: Freeze-drying and gamma irradiation are commonly used for preservation and sterilization in bone banking. The cumulative effects of preparation and sterilization of cancellous graft material have not been adequately studied, despite the clinical importance of graft material in orthopaedic surgery. Taking benefit from the symmetry of the left and right femoral heads, the influence of lipid extraction followed by freeze-drying of a femoral head and a final 25-kGy gamma irradiation was determined, with the nonirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 16 publications
5
94
1
1
Order By: Relevance
“…Within the fibrils, such molecular stretching competes with intermolecular sliding and breaking of weak and strong bonds between TC molecules, both sliding motions provide the basis for large plastic strains without catastrophic failure. 7 At the mineralized collagen fibril level, continuous glide between TC molecules and between hydroxyapatite (HA) particles and these molecules, initiated by slip at the HA-TC molecule interface, enables a large regime of dissipative deformation once plastic yielding begins. Such molecular behavior of the protein and mineral phases during large-scale deformation of the mineralized collagen fibrils, in addition to representing a mechanism of plasticity, provides for intrinsic toughening and enhanced fracture resistance through the formation of plastic zones around crack-like defects [77,78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the fibrils, such molecular stretching competes with intermolecular sliding and breaking of weak and strong bonds between TC molecules, both sliding motions provide the basis for large plastic strains without catastrophic failure. 7 At the mineralized collagen fibril level, continuous glide between TC molecules and between hydroxyapatite (HA) particles and these molecules, initiated by slip at the HA-TC molecule interface, enables a large regime of dissipative deformation once plastic yielding begins. Such molecular behavior of the protein and mineral phases during large-scale deformation of the mineralized collagen fibrils, in addition to representing a mechanism of plasticity, provides for intrinsic toughening and enhanced fracture resistance through the formation of plastic zones around crack-like defects [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…At the high dose end (>10 kGy), gamma irradiation is commonly used to terminally sterilize allograft tissues and bones [2][3][4][5], and has been proven to be very potent sterilization agent with the ability to effectively penetrate tissue. However, gamma irradiation is also known to adversely affect the mechanical and biological properties of tissue in a dose-dependent manner by degrading the collagen [6][7][8][9][10][11][12][13][14]. Specifically, gamma rays split polypeptide chains; in wet specimens, irradiation causes release of free radicals via radiolysis of water molecules that induces cross-linking reactions in collagen molecules [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has successfully been applied for sterilization of bone allografts in orthopedic surgery [6;7]. However, the radiation doses used (25 to 40 kGy) often reduce the mechanical stability of the bone grafts which might cause the implant to fail [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to changes in mechanical properties of bone by gamma irradiation, it has been used with some caution in clinical practice-especially in load-bearing applications. Irradiated morselized bone was found to be less strong, less stiff and significantly more brittle than fresh-frozen control bone when tested in compression models (Cornu et al 2000). However, it has been shown that irradiated freeze-dried impacted grafts provide a more stable femoral reconstruction than fresh-frozen grafts when tested in a hip simulator (Cornu et al 2003).…”
mentioning
confidence: 99%